Cotidiano del cuidado de enfermería desde la perspectiva del paciente hospitalizado - Aranda Mendoza, César Alexander (2019)
The present investigation began from the question how is the nursing care daily from the perspective of the hospitalized patient in the Medicine Service of a Hospital. The type of study is of a qualitative type with a phenomenological trajectory; This type of research allows us to understand and deepen human experiences, as well as to explore and investigate, experiences, perspectives and significant opinions of patients. The data collection was done through the semi-structured interview. The study sample consisted of 16 adult hospitalized patients. From the analysis of the discourses the results were organized and the phenomenological reduction was carried out in order to determine and select the essential parts, with five meaning units: Patients perceive that the nurses treat them with insensitivity and indifference, limitation in communication , patients' requirements to improve nursing care, some nurses treat well, care for the patient, are attentive and cordial, patients perceive that the work of the nurse prevents the care dedicated to them by the other activities that have to comply. The findings show that patients live in constant pre-occupation, occupation, require change in the improvement of care that by the inautencidad (indifference) of the nurses to provide a much more personalized attention, give him enough confidence to express what they feel. However, there is an increasing requirement for cure that is care that is not given to them.